Understanding the diversity of wetland-based livelihoods in the Limpopo River basin - (:unkn) unknown (My University, 2008)
Wetlands provide a wide range of ecosystem services that support livelihoods of many rural communities in Southern Africa. In the Limpopo River Basin, which is characterized by a semi-arid climate and scarce water resources, rural people use wetlands for agricultural production thanks to their rich soils and permanent supply of water. However, agricultural production has the potential of altering the pristine state of wetlands and consequently jeopardizing the provision of future ecosystem services. As part of an effort to improve management of wetlands, the present study assessed the socio-economic determinants of household use of wetlands in two sites in the Limpopo River basin. A stratified random sampling technique was used to select 143 and 131 households respectively in the two sites. Using the sustainable livelihood framework, information was collected from households on their assets and use of wetlands. Multivariate analysis was used to categorize households according to their wetland uses. Multinomial logit models were then used to examine the factors that influence household choices on use of wetland resources. The results highlighted the diversity of wetland uses, their relationships with other assets endowment and their contribution to livelihoods. Generally, households in Intunjambili were more frequently engaged in wetland activities than in Ga-Mampa and therefore more reliant on its resources. The nature of household use of wetlands, strongly differentiated across households, appeared to be site-specific and highly influenced by socio-economic factors. At one site wealthier households were more likely to engage in wetland cropping than poor households, while the opposite was observed in the other site. In both sites poor households were more likely to engage in extraction of natural wetland products (reeds, sedges, edible plants) than wealthier households. The first policy implication is that any program that seeks to mitigate the impact
Keywords: African Research